2020
DOI: 10.15171/ijhpm.2019.142
|View full text |Cite
|
Sign up to set email alerts
|

A Decomposition of Life Expectancy and Life Disparity: Comparison Between Hong Kong and Japan

Abstract: Background: Life expectancy and life disparity are 2 useful indicators to assess the health condition of a society. Both Hong Kong and Japan have one of the longest life expectancies in the world. Recently, Hong Kong has overtaken Japan and topped the life expectancy rankings. However, whether Hong Kong has also outperformed Japan in life disparity is still unknown. Methods: Decomposition analyses have been conducted to evaluate age-specific contributions to the changes in life expectancy and life disparity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…In Hong Kong, life disparity increased alongside increased threshold age with no apparent slowdown in e0 gains. 8 By contrast, we show that in the USA, life disparity increased alongside slowdown and decreases in e0. Thus, it may be that the threshold age in the USA also fell, in contrast to the increase in Hong Kong, and a rising life disparity in the context of stalling or falling threshold age may also indicate population health challenges.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…In Hong Kong, life disparity increased alongside increased threshold age with no apparent slowdown in e0 gains. 8 By contrast, we show that in the USA, life disparity increased alongside slowdown and decreases in e0. Thus, it may be that the threshold age in the USA also fell, in contrast to the increase in Hong Kong, and a rising life disparity in the context of stalling or falling threshold age may also indicate population health challenges.…”
Section: Discussioncontrasting
confidence: 60%
“…A study of two populations with increasing longevity, Japan and Hong Kong, showed that life disparity can increase where no adverse trends in mortality are occurring at any age, and while e0 continues to increase. 8 Conversely, analysis of the burden of COVID-19 on mortality in the UK found lifespan inequality decreased during the first year of the pandemic, while e0 also decreased. 3 In both examples, the utility of life disparity is as complementary to e0 -a rising life disparity in the context of stagnating or falling e0 may indicate emerging public health challenges in a given population but a decreasing life disparity in isolation does not indicate a healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Life expectancy (LE) at birth indicates the mortality pattern in all age groups, which estimates the average number of years that a newborn is expected to live, provided that the current pattern of mortality does not change [ 1 ]. Globally, this indicator is frequently used as a tool for measuring the progress and backwardness of countries.…”
Section: Introductionmentioning
confidence: 99%